Application of Social Cognitive Theory in Modeling Farmers' Behavior to Encourage Them to Choose Low-Water-Demand Cropping Patterns - Amirreza Nasiri; Mahdi Mashhadi; Seyyed Ahmadreza Shahangian; Reza Kerachian (تحقیقات منابع آب ایران, 2025)
Promoting the cultivation of low-water-demand crops, such as medicinal plants, instead of high-water-demand crops is one of the recommended strategies for reducing water consumption in agriculture and combating droughts. However, voluntary adoption and active participation of farmers are key to the success of such initiatives. Therefore, in promoting such behavior, it is essential to have a proper understanding of farmers' behaviors and the factors influencing them. Considering the fundamental role of environmental psychology in understanding human behavior, this article seeks to examine the socio-psychological factors that affect farmers' behavior regarding the shift in cropping patterns from high-water-demand crops to medicinal plants. In this regard, a structured questionnaire was developed based on social cognitive theory following an in-depth review of the existing literature. After confirming the content and face validity of the questionnaire by farmers and experts, as well as verifying its reliability through a pilot sample using Cronbach's alpha coefficient, the final version of the questionnaire was distributed among the target population of the study, namely farmers residing in the Sojasrood plain in Zanjan province. Ultimately, data were collected through face-to-face interviews with 184 out of approximately 400 farmers, which was adequate in comparison to research standards. Additionally, for data analysis, a structural equation modeling approach using partial least squares was employed through SmartPLS software. After confirming the measurement model through the evaluation of construct validity and reliability, which includes convergent and discriminant validity, the results of the structural model showed that social cognitive theory could predict respectively 56% and 49% of the variance in farmers' intention and behavior towards cultivating medicinal plants. Furthermore, outcome expectancies were found to be the most significant predictor of intention while intention itself emerged as the most crucial determinant of the behavior. The findings of this study not only provide valuable insights for researchers but also serve as an effective guide for policymakers in implementing more efficient policies. In this context, various strategies such as cultural promotion and education of farmers have been proposed to encourage the cultivation of medicinal plants among farmers.